TOKSISITAS AKUT EKSTRAK METANOL RUMPUT LAUT COKELAT Sargassum echinocarpum - Muhamad Firdaus; Made Astawan; Deddy Muchtadi; Tutik Wresdiyati; Sarwono Waspadji; Setyawati S Karyono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
The aim of this study was to evaluate acute toxicity of methanol extract of Sargassum echinocarpum on male and female of mice (Mus musculus) strain BALB/c two month age. S. echinocarpum was obtained from Talango Island in April 2008. The powder of S. echinocarpum was macerated by methanol (1:3) at 4 °C for 3 x 24 hours, then concentrated, dried, and extracted. The extract was screened to observe the phytochemical compounds. For acute toxicity extracts was given orally and once on one hour before feeding. The dose treatments were 0; 625; 1250; 2500; and 5000 mg/kg body weight (BW). Parameters measured were phytochemical contain, body weight during the study, 50 percent of lethal doses, and histology score of liver and kidney. The phytochemical study showed that methanol extract of S. echinocarpum contained tannins, polyphenols, saponins, glycosides, and steroids. On 1250 mg/kg BW or more, methanol extract of S. echinocarpum inhibited the increasing of body weight on mice, but, until 5000 mg/kg BW, it did not cause mortality on mice. On 1250 mg/kg BW or more, methanol extracts caused necrosis on hepatocyt and tubulus.Key words: acute toxicity, methanol extract, Sargassum echinocarpum